Combined effect of Neolamarckia cdamba leaves and electroporation method on HeLa cell anti- proliferation process - Abdul Jamil, Muhammad Mahadi; Abd Rahman, Nur Adilah; Mohamad Ishak, Daing Nor Farhanah; Adon, Mohd Nazib; Chew, Chang Choon; Ambar, Radzi; Abdul Wahab, Ridhwan (Institute of Electrical and Electronics Engineers Inc., 2019)
This study suggests that natural sources may become an important tool in treating cancer. Neolamarckia cadamba (NC) leaves also well-known as “Anthocephalus Cadamba”, is a precious plant in Ayurvedic medicine. HeLa cells are one of the examples of eukaryotic cells type. It is derived from human cervical cancer cells. This experiment is conducted in different concentrations of NC Leaves (1μg/ml, 5μg/ml, 10μg/ml, 20μg/ml, 30μg/ml, 40μg/ml, 50μg/ml, 60μg/ml, 70μg/ml, 80μg/ml, 90μg/ml and 100μg/ml) for 48 hours. This experiment's result proves that the anti-cancer properties of the extract of NC leaves are by increasing the concentration of extract, the numbers of cell viability will decrease. For contribution, the process of NC leaves extract will be combined with the electroporation process to investigate the effect on HeLa cell. Electroporation parameters used for this study were (voltage 600v/cm, pulse duration 5ms, single pulse).